Chemical Composition and Anti‐Alzheimer's Disease‐Related Activities of a Functional Oil from the Edible Seaweed Hizikia fusiforme. Issue 8 (30th July 2020) - Yang, Wen‐Cong; Zhang, Yuan‐Yuan; Li, Ya‐Juan; Nie, Ying‐Ying; Liang, Jin‐Yue; Liu, Ya‐Yue; Liu, Jing‐Shan; Zhang, Yong‐Ping; Song, Cai; Qian, Zhong‐Ji; Zhang, Yi
Abstract: Cholinergic disorder, oxidative stress, and neuroinflammation play important roles in the pathology of Alzheimer's disease. To explore the healthy potential of the edible seaweed Hizikia fusiforme on this aspect, a functional oil (HFFO) was extracted from this alga and investigated on its constituents by gas chromatography‐mass spectrometry (GC/MS) in this study. Its anti‐Alzheimer's related bioactivities including acetylcholinesterase (AChE) inhibition, antioxidation, and anti‐neuroinflammation were evaluated, traced, and simulated by in vitro and in silico methods. GC/MS analysis indicated that HFFO mainly contained arachidonic acid (ARA), 11, 14, 17‐eicosatrienoic acid (ETrA), palmitic acid, phytol, etc. HFFO showed moderate AChE inhibition and antioxidant activity. Bioactivity tracing using commercial standards verified that AChE inhibition of HFFO mainly originated from ARA and ETrA, whereas antioxidant activity mainly from ARA. Lineweaver−Burk plots showed that both ARA and ETrA are noncompetitive AChE inhibitors. A molecular docking study demonstrated low CDOCKER interaction energy of −26.33 kcal/mol for ARA and −43.70 kcal/mol for ETrA when interacting with AChE and multiple interactions in the ARA (or ETrA)−AChE complex. In the anti‐neuroinflammatory evaluation, HFFO showed no toxicity toward BV‐2 cells at 20 μg/mL and effectively inhibited the production of nitroxide and reduced the level of reactive oxygen species in lipopolysaccharide‐induced BV‐2 cells. The results indicated that HFFO could be used in functional foods for its anti‐Alzheimer's disease‐related activities. Abstract :